To solve for f, you need to isolate/get the variable by itself in the equation:
4(0.5f - 0.25) = 6 + f Distribute 4 into (0.5f - 0.25)
(4)0.5f + (4)(-0.25) = 6 + f
2f - 1 = 6 + f Subtract f on both sides to get "f" on one side of the equation
2f - f - 1 = 6 + f - f
f - 1 = 6 Add 1 on both sides to get "f" by itself
f - 1 + 1 = 6 + 1
f = 7
PROOF
4(0.5f - 0.25) = 6 + f Substitute/plug in 7 into "f" since f = 7
4(0.5(7) - 0.25) = 6 + 7
4(3.5 - 0.25) = 13
4(3.25) = 13
13 = 13
Answer:
12
Step-by-step explanation:
For this question, simply plug in -2 for x:
![g(-2)=2(-2)^2-4(-2)-4\\g(-2)=2(4)+8-4\\g(-2)=8+8-4\\g(-2)=12](https://tex.z-dn.net/?f=g%28-2%29%3D2%28-2%29%5E2-4%28-2%29-4%5C%5Cg%28-2%29%3D2%284%29%2B8-4%5C%5Cg%28-2%29%3D8%2B8-4%5C%5Cg%28-2%29%3D12)
Hope this helps!!
The answer is 78.5 because the formula to find area is πr2 so the radius is 5ft π is 3.14 so 3.14 times 5 and the 2 on top of r means the u have to do 5 times 5 which is 25 now it's real simple do 3.14 times 25 which is 78.5 I HOPE THIS HELPS=)
V= wlh so the answer is 56.25 or 56 1/4
Answer:
8,613
Step-by-step explanation: